Dispersion of chain-like particles, coating paint, and method for manufacturing a film-coated substrate.
Patent Information
- Application Number
- JP2026180586
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-01-29
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-16
AI Technical Summary
【0009】 本開示の一態様にかかる鎖状粒子の分散液は、低いpH領域でも良好な分散安定性を備えている。また、この分散液を含む塗料を用いて形成された膜は、粒子の含有量が少なくても、表面抵抗値が低く、基材との密着性および膜強度等に優れている。
Smart Images

Figure 2026169301000001 
Figure 2026169301000002 
Figure 2026169301000003
Abstract
Description
[Technical Field]
[0001] This invention relates to chain-like particles in which ATO particles are linked together. [Background technology]
[0002] Conventionally, a transparent conductive film has been formed on the surface of transparent plastic substrates used in LCD displays, organic EL displays, and micro-LED displays, etc., to prevent static electricity.
[0003] For example, transparent conductive films are known that incorporate conductive oxide particles such as antimond-doped tin oxide (ATO) or tin-doped indium oxide (ITO) as a matrix component. Such conductive particles are often incorporated in large quantities into the film to enhance its antistatic properties. However, the color of the conductive particles may lead to insufficient transparency of the film and deterioration of haze. Furthermore, this can negatively impact properties such as adhesion to the substrate, film strength, and production costs.
[0004] Therefore, it has been proposed to form a transparent conductive film with excellent conductivity even when the number of particles in the film is small, by linking conductive oxide particles in a chain-like manner to increase contact between the particles (see Japanese Patent Publication No. 9-31238 and Japanese Patent Publication No. 2006-339113). [Overview of the project] [Problems that the invention aims to solve]
[0005] Conventional chain-like particles have a high isoelectric point, resulting in insufficient dispersion stability in low pH ranges. Therefore, in low pH ranges, it is difficult to obtain a uniform chain structure, to sufficiently reduce alkali metal components, and to maintain the chain structure over long periods. When such chain-like particles are incorporated into paints, it can be difficult to maintain the chain structure, or the chain particles may aggregate. This can make it difficult to obtain good surface resistance, haze, and film hardness in films with low particle concentrations. [Means for solving the problem]
[0006] The inventors have found that by using chain-like particles formed by linking ATO particles prepared in a silicon dioxide-containing system, dispersion stability is improved even in low pH ranges. Specifically, in one embodiment of the present disclosure, the dispersion of chain-like particles has an average particle diameter of 5 to 20 nm, an average number of linked ATO particles of 3 to 40, an isoelectric point of less than pH 2.0, and the chain-like particles contain silicon dioxide.
[0007] These chain-like particles contain silicon oxide, tin oxide, and antimony oxide. Preferably, silicon oxide accounts for 0.5 to 10% by weight, tin oxide for 70 to 95% by weight, and antimony oxide for 4.5 to 29.5% by weight of the total amount. Furthermore, these chain-like particles are dispersed in a solvent (water or an organic solvent). When an acid (for example, hydrochloric acid) is added to the resulting dispersion to adjust the pH to 1.0, the average particle size of the chain-like particles becomes 100 nm or less.
[0008] A dispersion of these chain-like particles can be produced by following the steps outlined below in order. Step (a): A suspension is prepared by suspending ATO powder in an aqueous solution containing 0.05 to 5.0% by weight of an alkali metal hydroxide. A dispersion of ATO particles is prepared by dispersing this suspension in a silicon dioxide-containing system. Step (b): This dispersion is subjected to hydrothermal treatment. Step (c): With the solid content concentration of the dispersion less than 10% by weight, an alkaline component is added to the dispersion to adjust the pH of the dispersion to 4 or higher, then the solid content concentration of the dispersion is adjusted to 15% by weight or higher, and then the pH of the dispersion is lowered to 1-3. Step (d): Add R to this dispersion. n -SiX 4-n Add the organosilicon compound represented by [formula]. Here, R is an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, and may be the same or different from each other. n is an integer from 0 to 3. Examples of substituents include epoxy groups, (meth)acryloyloxy groups, mercapto groups, amino groups, phenyl groups, and isocyanate groups. X is one (or at least one) of an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, a halogen atom, or a hydrogen atom. By drying the dispersion of the chain-like particles obtained in this way, the chain-like particles can be obtained as a powder. [Effects of the Invention]
[0009] A dispersion of chain-like particles according to one aspect of this disclosure exhibits good dispersion stability even in low pH ranges. Furthermore, a film formed using a paint containing this dispersion has low surface resistance, excellent adhesion to the substrate, and superior film strength, even with a low particle content. [Modes for carrying out the invention]
[0010] The chain-like particles in this embodiment are linked ATO (antimond-doped tin oxide) particles and contain silicon dioxide. In other words, they are chain-like ATO (antimond-doped tin oxide) particles containing silicon dioxide. Here, the average particle diameter of the ATO particles is 5 to 20 nm. The average number of linked chain-like particles is 3 to 40, and the isoelectric point of the chain-like particles is less than pH 2.0.
[0011] If the average particle diameter of the ATO particles (primary particles) is not in the range of 5 to 20 nm, it is difficult to obtain chain-like particles with an average linkage of 3 to 40. Obtaining particles (primary particles) with an average particle diameter smaller than 5 nm is industrially difficult, and even if obtained, primary particles have low stability, making them prone to aggregation and difficult to form into a chain-like shape. When the average particle diameter exceeds 20 nm, contact and aggregation between primary particles are difficult to occur, so many primary particles remain monodisperse. In other words, it is difficult to obtain a chain-like shape with an average linkage of 3 or more. For this reason, coatings with a low particle content may not be able to obtain a low surface resistance value. The average particle diameter of the ATO particles is preferably 6 to 15 nm, and more preferably 7 to 12 nm.
[0012] Furthermore, if the average number of linked chain particles falls within the above range, a film with a low surface resistance can be obtained even with a low particle content. If the average number of linked chain particles is less than 3, it is difficult to obtain a low surface resistance in a film with a low particle content. It is difficult to obtain chain particles with an average number of linked chain particles exceeding 40. Even if obtained, the stability of the coating may decrease or the haze of the film may increase. The lower limit of the average number of linked chain particles is preferably 5, and more preferably 7. The upper limit of the average number of linked chain particles is preferably 30, and more preferably 20.
[0013] Further, the isoelectric point of the chain-shaped particles is less than pH 2.0. In general, for inorganic oxide particles, when the pH of a solution changes, the potential (zeta potential) on the particle surface changes. This potential becomes zero at a specific pH value. The pH value at this point is the isoelectric point. At the isoelectric point, the potential on the particle surface disappears, so the electrostatic repulsive force is lost, and the particles tend to aggregate. Normally, the isoelectric point of ATO particles is around 4. On the other hand, the isoelectric point of the chain-shaped particles according to the present embodiment is less than 2.0. When the isoelectric point is 2.0 or higher, the stability in the low pH region is insufficient, so three-dimensional aggregation is likely to occur. Therefore, a uniform chain structure is difficult to form. In addition, when dealkalization is performed, the pH decreases, which may cause the particles to aggregate. Furthermore, since the aggregation of particles proceeds even after the chain shape is formed, there is a risk that it may be difficult to maintain the chain structure for a long period of time. The isoelectric point is preferably 1.8 or less, more preferably 1.5 or less, and even more preferably 1.0 or less.
[0014] These chain-shaped particles contain silicon oxide, tin oxide, and antimony oxide. Based on the total weight of these three components, the content of silicon oxide is preferably 0.5 to 10 wt%. The content of tin oxide is preferably 70 to 95 wt%. The content of antimony oxide is preferably 4.5 to 29.5 wt%. When the content of silicon oxide increases, the proportion of non-conductive substances increases, so that the surface resistance value of the film becomes high. Therefore, the content of silicon oxide is preferably 10 wt% or less. When the content of silicon oxide is less than 0.5 wt%, the isoelectric point may exceed 2.0. The content of silicon oxide is preferably 0.8 to 8 wt%, and more preferably 3.0 to 6.0 wt%.
[0015] When the content of tin oxide or antimony oxide deviates from the above ranges (that is, when tin oxide is less than 70 wt% or exceeds 95 wt%, or when antimony oxide is less than 4.5 wt% or exceeds 29.5 wt%), the conductivity of the chain-shaped particles decreases, which may lead to an increase in the surface resistance value of the film.
[0016] The chain particles described above are dispersed in water or an organic solvent. When an acid is added to the obtained dispersion so that the pH becomes 1.0, the average particle diameter of the chain particles is 100 nm or less. When the stability on the low pH side is low, the average particle diameter of the chain particles may exceed 100 nm. That is, when the pH is lowered, the chain particles tend to aggregate, and the average particle diameter of the chain particles tends to increase. As a result, the haze of the coating film may increase. The average particle diameter of the chain particles is preferably 90 nm or less, and more preferably 70 nm or less.
[0017] The acid used here is not particularly limited as long as it can adjust the pH to 1.0. The acid is preferably an inorganic acid such as hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid, or an organic acid such as formic acid and acetic acid.
[0018] In addition, the amount of the alkali metal contained in this dispersion is preferably 0.05% by weight or less. The smaller the content of the alkali metal, the more the chain structure is maintained in the coating film, so that a film with a low surface resistance value and a film with low haze can be easily obtained. The content of the alkali metal is more preferably 0.03% by weight or less, and still more preferably 0.01% by weight or less. Here, the alkali metal refers to Li, Na, K, Rb, Cs, and Fr.
[0019] In addition, water or an organic solvent is used as the dispersion medium. As the organic solvent, a solvent that can uniformly disperse the particles and can dissolve or disperse additives such as a matrix-forming component and a polymerization initiator is used. Among them, the hydrophilic solvents shown in Table 1 are preferable. In particular, water or alcohols are preferable. These may be used alone or in combination of two or more kinds.
[0020] [Table 1]
[0021] [Method for producing dispersion liquid of chain particles] The chain-like particles of this embodiment can be manufactured by following the steps below in order. Step (a): A suspension is prepared by suspending ATO powder in an aqueous solution containing 0.05 to 5.0% by weight of an alkali metal hydroxide. A dispersion of ATO particles is prepared by dispersing this suspension in a system containing silicon dioxide. This step is expected to coat the surface of at least some of the ATO particles with silicon dioxide. However, it is not guaranteed that the entire surface will be coated. Step (b): This dispersion is subjected to hydrothermal treatment. Step (c): An alkaline component is added to the hydrothermally treated dispersion while the solid content concentration of the dispersion is less than 10% by weight to adjust the pH of the dispersion to 4 or higher. Subsequently, the solid content concentration of the dispersion is adjusted to 15% by weight or higher, and then the pH of the dispersion is lowered to 1-3. This step promotes the chain formation of the ATO particles, resulting in chain particles with a large number of links. Process (d): After process (c), "R n -SiX 4-n An organosilicon compound represented by is added to the dispersion. Here, n is an integer from 0 to 3. R is an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, and may be the same or different from each other. Substituents include epoxy groups, (meth)acryloyloxy groups, mercapto groups, amino groups, phenyl groups, and isocyanate groups. X is an alkoxy group, hydroxyl group, halogen atom, or hydrogen atom having 1 to 4 carbon atoms. By including this step, the dispersibility of the chain particles can be maintained when preparing a paint using this dispersion. In addition, it is possible to prevent a decrease in the number of linked chain particles in the paint. The dispersion obtained in step (a) preferably contains 10 to 40% by weight of the ATO component. Silicon oxide is preferably present in an amount of 0.1 to 5.0% of the ATO component content. Alkali metals are preferably present in an amount of 0.1 to 20.0% of the ATO component content.
[0022] Through such a process, chain particles in which ATO particles (average particle diameter 5 to 20 nm) are linked can be produced. The average linkage number of the chain particles is 3 to 40, and the isoelectric point of the chain particles is less than pH 2.0. Hereinafter, each step will be described in detail.
[0023] [Step a] First, a powder of ATO particles is prepared. A conventionally known ATO particle powder can be used. The ATO particle powder (hereinafter referred to as ATO powder) preferably has a specific surface area measured by the BET method of 40 m 2 / g to 180 m 2 / g. If the specific surface area is less than 40 m 2 / g, the average primary particle diameter after dispersion becomes too large, and a chain structure may not be formed. If the specific surface area is larger than 180 m 2 / g, it becomes difficult to disperse the ATO particles. Even if the ATO particles can be dispersed, the ATO particles are small, so the stability of the ATO particles is low. Therefore, the ATO particles tend to aggregate, and a chain shape is hardly formed. The specific surface area is more preferably 60 to 150 m 2 / g, and further preferably 80 to 140 m 2 / g.
[0024] The weight ratio of tin oxide to antimony oxide contained in the ATO powder is preferably 70:30 to 95:5. If the weight ratio is outside this range (that is, when tin oxide is less than 70 wt% or more than 95 wt%, or when antimony oxide is less than 5 wt% or more than 30 wt%), the conductivity of the ATO particles decreases, which may increase the surface resistance value of the film.
[0025] A suspension is prepared by suspending such ATO powder in an aqueous solution containing 0.05 to 5.0% by weight of an alkali metal hydroxide. Examples of alkali metal hydroxides include sodium hydroxide, potassium hydroxide, and lithium hydroxide. If the concentration of alkali metal hydroxide is less than 0.05% by weight, the amount of silicon dioxide dissolved will be insufficient, and the isoelectric point may exceed 2.0. It is preferable that the concentration of alkali metal hydroxide be 0.1% by weight or more. On the other hand, if the concentration of alkali metal hydroxide exceeds 5.0% by weight, it becomes difficult to remove the alkali metal hydroxide in subsequent steps. Also, the amount of dissolved silicon dioxide becomes too large, resulting in a large amount of silicon dioxide on the surface of the ATO particles. Therefore, it becomes difficult to form a film with a low surface resistance. It is preferable that the concentration of alkali metal hydroxide be 3.0% by weight or less, and more preferably 1.0% by weight or less.
[0026] Next, this suspension is dispersed in an environment where silicon dioxide is present. That is, a dispersion of ATO particles is prepared by performing the dispersion treatment in a system where silicon dioxide is present. At this time, it is sufficient that the silicon dioxide raw material is in contact with the suspension. Therefore, the silicon dioxide raw material may be added to the suspension beforehand, or it may be added during the dispersion treatment. Alternatively, the equipment used for the dispersion treatment may contain silicon dioxide components. For example, beads used as a dispersion medium, or the container holding the suspension, can be used as silicon dioxide raw materials. ATO powder containing silicon dioxide components may also be used. Examples of silicon dioxide raw materials to be added to the suspension include silicic acid solution, sodium silicate, silica sol, and silica powder.
[0027] When adding silicon dioxide to a suspension, it is preferable to add silicon dioxide in an amount equivalent to 0.1 to 5% of the ATO powder volume. If the amount of silicon dioxide added is greater than 5%, the amount of silicon dioxide on the surface of the ATO particles will increase, which may raise the surface resistance of the film. Also, if silicon dioxide powder is used as the silicon dioxide component, the silicon dioxide powder may not dissolve completely and remain as a residue, which may increase the haze of the coating.
[0028] If the beads or container contain silicon dioxide, the silicon dioxide will dissolve due to the alkali metal components in the suspension, thus achieving the same effect as when silicon dioxide is added. In this case as well, the amount of silicon dioxide in the suspension is preferably 0.1 to 5% relative to the amount of ATO powder.
[0029] Equipment used for dispersion processing includes Henschel mixers, homomixers, homogenizers, and bead mills. Among these, bead mills are preferred because they can perform industrial-scale dispersion processing. Examples of bead mills include Batch SAND from Kansai Paint Co., Ltd., MSC Mill from Nippon Coke Industries Co., Ltd., Ultra Apex Mill from Hiroshima Metal & Machinery Co., Ltd., Star Mill and Nano Getter from Ashizawa Finetech Co., Ltd., Neo-Alpha Mill from AIMEX Co., Ltd., and Dyno Mill from Shinmaru Enterprises Co., Ltd.
[0030] When using a bead mill for dispersion processing, beads with a size of 1.0 mm or less are used as the dispersion medium, such as zirconia beads (YTZ series from Tosoh Corporation), alumina beads (TB series from Daimei Chemical Industry Co., Ltd.), or glass beads (L series from Unitika Corporation).
[0031] [Step b] Next, the dispersion of ATO particles is subjected to hydrothermal treatment. Hydrothermal treatment makes it easier to lower the isoelectric point to 2.0 or below. At this time, the amount of dissolved oxygen in the dispersion is preferably 3 mg / L or more. If the amount of dissolved oxygen is less than 3 mg / L, the isoelectric point will not be sufficiently lowered during hydrothermal treatment. Therefore, there is a risk that the particles will aggregate when the pH is lowered, and it may be difficult to form a uniform chain structure. Even if a chain structure is obtained, the average number of linked particles may exceed 40. The amount of dissolved oxygen in the dispersion is preferably 10 mg / L or more, and more preferably 20 mg / L or more.
[0032] If the dissolved oxygen content of the dispersion obtained in step a is 3 mg / L or more, the dispersion can be subjected to hydrothermal treatment as is. If the dissolved oxygen content is less than 3 mg / L, the dissolved oxygen content of the dispersion is increased by bubbling oxygen gas or adding hydrogen peroxide.
[0033] Hydrothermal treatment is preferably carried out at 100-300°C for 1-64 hours. If the treatment temperature is below 100°C, antimony doping will not proceed, and the surface resistance of the film will not decrease sufficiently. On the other hand, if the treatment temperature exceeds 300°C, doping will not proceed any further, and expensive heat-resistant and pressure-resistant equipment will be required. If the treatment time is less than 1 hour, antimony doping will be insufficient, and the surface resistance of the film will not decrease sufficiently. If the treatment time is longer than 64 hours, antimony doping will not proceed any further, resulting in decreased productivity.
[0034] [Process c] Next, after step b, when the solid content concentration of the dispersion is less than 10% by weight, an alkaline component is added. This adjusts the pH of the dispersion to 4 or higher. When the pH of the dispersion is 4 or higher, the solid content concentration can be steadily increased thereafter. If the pH of the dispersion is less than 4, the particles are likely to aggregate during the process of increasing the solid content concentration, which may prevent the formation of a chain-like structure with an average number of links between 3 and 40. The pH of the dispersion is preferably 6 or higher, and more preferably 7 to 10.
[0035] Examples of alkaline components added here include sodium hydroxide, potassium hydroxide, aqueous ammonia, and TMAH. In order to reduce the alkali metal concentration later, the alkaline component is preferably aqueous ammonia or TMAH.
[0036] Subsequently, the solid content concentration of the dispersion is adjusted to 15% or higher. Known methods (such as distillation or filtration) can be used to adjust the solid content concentration. If the solid content concentration is less than 15%, subsequent particle chain formation is less likely to occur, and the number of linked particles tends to be less than 3. The solid content concentration is preferably 15 to 30% by weight. If the solid content concentration is 30% by weight or higher, the average number of linked particles may exceed 40. The solid content concentration is more preferably in the range of 18 to 25% by weight.
[0037] After adjusting the solid content concentration of the dispersion to 15% by weight or higher, the pH of the dispersion is lowered to between 1 and 3. That is, the pH is adjusted while the solid content concentration is 15% by weight or higher. The pH can be lowered by adding an acid or by dealkalization. In particular, it is preferable to perform ion exchange treatment using an ion exchange resin. Furthermore, the method of adding an acid may also be added. As the ion exchange resin, an H-type cation exchange resin is suitable. If the pH of the dispersion is less than 1, the average number of linked chain particles may exceed 40. On the other hand, if the pH of the dispersion is higher than 3, chain formation may not proceed, and the average number of linked particles may be less than 3.
[0038] [Step d] Next, add R to this dispersion. n -SiX 4-n An organosilicon compound represented by is added. Here, n is an integer from 0 to 3. R is an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, which may be the same or different from each other. Examples of substituents include epoxy groups, (meth)acryloyloxy groups, mercapto groups, amino groups, phenyl groups, and isocyanate groups. X is an alkoxy group, hydroxyl group, halogen atom, or hydrogen atom having 1 to 4 carbon atoms. At this time, it is preferable to add an alcohol to the dispersion.
[0039] The amount of organosilicon compound added is preferably 10-35% of the amount of ATO particles present in the dispersion. If the amount of organosilicon compound added is less than 10%, chain-like particles with an average linkage of 3-40 in the dispersion may become chain-like particles with an average linkage of less than 3 in the coating. Even if the linkage is maintained, the dispersibility of the chain-like particles in the coating may be insufficient, which may result in increased film haze or increased surface resistance. If the amount of organosilicon compound added exceeds 35% by weight, the surface of the ATO particles may be thickly covered with the organosilicon compound, which may increase the surface resistance of the coating. The amount of organosilicon compound added is more preferably 15-25% by weight. Note that the appropriate amount of addition varies depending on the type of organosilicon compound, as well as the particle size and linkage of the ATO particles.
[0040] Table 2 shows examples of organosilicon compounds. We can use these organosilicon compounds individually or in combination of two or more. It is preferable to use compounds in which n is 0 or 1.
[0041] [Table 2]
[0042] The alcohols added in this process are preferably those listed in Table 1. We can use these individually or in combination of two or more.
[0043] In this case, the amount of alcohol added is preferably 10 to 1000% of the total volume of the dispersion of chain particles. If the amount of alcohol added is less than 10%, the added organosilicon compound may not dissolve well, and a uniform coating may not be formed on the chain particles. In this case, the average number of linked chain particles may exceed 40, or the chain particles may be partially and thickly covered, which may increase the surface resistance of the coating. Also, if the amount of alcohol added exceeds 1000%, the links of the chain particles may break due to dilution, and the average number of linked chain particles may fall to less than 3. The amount of alcohol added is more preferably 30 to 500%, and even more preferably 50 to 200%.
[0044] Furthermore, it is preferable to heat the dispersion containing the alcohol at a temperature of 30°C or higher, but below the boiling point of the solvent used. If the heating temperature is too low, the reaction may take a long time, or unreacted organosilicon compounds may remain, depending on the type and amount of organosilicon compounds and alcohol added. The more unreacted organosilicon compounds there are, the more likely the paint's stability and film hardness will decrease.
[0045] Furthermore, after adding the organosilicon compound to the dispersion, an acid catalyst may be added to the dispersion as needed. Examples of acid catalysts include inorganic acids (such as hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid) or organic acids (such as formic acid and acetic acid).
[0046] The dispersion of chain-like particles obtained through this process can be used directly as a coating for forming a transparent film. If necessary, the solvent may be replaced with water or an organic solvent. Examples of equipment used for solvent replacement include a rotary evaporator and an ultrafiltration membrane. Solvent replacement improves the compatibility between the matrix components in the coating and the particles. Therefore, the occurrence of streaky unevenness and defects during coating is suppressed, and the appearance can be improved.
[0047] [paint] A coating for forming a transparent film can be prepared by combining the aforementioned dispersion of chain-like particles with a matrix-forming component and an organic solvent.
[0048] The solid content of the chain particles in the paint is preferably in the range of 0.06% to 7.5% by weight. If the solid content is less than 0.06% by weight, there are too few chain particles in the film, resulting in a high surface resistance. On the other hand, if the solid content exceeds 7.5% by weight, the film becomes noticeably discolored. A solid content of 0.1% to 6.0% by weight is more preferable. Furthermore, the total concentration of chain particles and matrix-forming components in the paint is preferably in the range of 3% to 50% by weight as solid content. If this total concentration is less than 3% by weight, the film thickness will be thin, and sufficient surface resistance and scratch resistance may not be obtained. If this total concentration exceeds 50% by weight, the viscosity of the paint will increase and its fluidity will decrease, resulting in poor coatability. Furthermore, the dispersibility of the chain particles in the paint will decrease, making it difficult to obtain a uniform film thickness. As a result, appearance defects such as uneven coating are likely to occur. A total concentration of 5% to 40% by weight is more preferable.
[0049] The organic solvent used in the paint can be any solvent that can disperse chain-like particles and dissolve or disperse matrix-forming components. Examples of such organic solvents include water, ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, butyl methyl ketone, cyclohexanone, methylcyclohexanone, dipropyl ketone, methyl pentyl ketone, diisobutyl ketone, acetylacetone, and acetoacetic acid esters, etc.), and the hydrophilic solvents shown in Table 1. These may be used individually or in combination of two or more.
[0050] As the matrix component, known organic resin binders (such as thermosetting resins and thermoplastic resins) and inorganic binders consisting of organosilicon compounds can be used. Examples of thermoplastic resins include polyester resins, polycarbonate resins, polyamide resins, polyphenylene oxide resins, thermoplastic acrylic resins, vinyl chloride resins, fluororesins, vinyl acetate resins, and silicone rubber. Examples of thermosetting resins include urethane resins, melamine resins, silicon resins, butyral resins, reactive silicone resins, phenolic resins, epoxy resins, unsaturated polyester resins, and thermosetting acrylic resins. The thermosetting resin may be UV-curable or electron beam-curable. The thermosetting resin may contain a curing catalyst. The matrix component may be a copolymer or modified form of two or more of the above-mentioned resins. These resins may be emulsion resins, water-soluble resins, and hydrophilic resins.
[0051] Suitable UV-curing resins used as matrix components include alkylene oxide-modified acrylic resins such as ethylene oxide-modified acrylic resins, propylene oxide-modified acrylic resins, and butylene oxide-modified acrylic resins. Alkylene oxide modification means having a block structure of alkylene oxides such as ethylene oxide (-CH2-CH2-O-) and propylene oxide (-CH2-CH2-CH2-O-).
[0052] In particular, by using ethylene oxide-modified acrylic resin or propylene oxide-modified acrylic resin, the ATO particles are surface-treated in the coating solution, resulting in high dispersion of the ATO particles without aggregation. Therefore, a film with low surface resistance and excellent transparency, light transmittance, and hardness can be obtained.
[0053] Furthermore, by including an unmodified acrylic resin along with an alkylene oxide-modified acrylic resin as the matrix component, a film with excellent hardness and adhesion can be obtained. Examples of unmodified acrylic resins include pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol hexaacrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, 2-ethylhexyl methacrylate, isodecyl methacrylate, n-lauryl acrylate, n-stearyl acrylate, 1,6-hexanediol dimethacrylate, perfluorooctyl ethyl methacrylate, trifluoroethyl methacrylate, and urethane acrylate, as well as mixtures thereof.
[0054] [Membrane-coated substrate] By using the paint described above, a coating containing chain-like particles and matrix components can be formed on the substrate.
[0055] Known materials such as sheets, films, or panels made from glass, polycarbonate, acrylic resin, polyethylene terephthalate (PET), or triacetylcellulose (TAC) can be used as substrates. Suitable substrate materials include TAC, polycarbonate, and acrylic resin. In particular, interference fringes can be suppressed by forming a transparent coating consisting of chain-like particles and matrix components on a TAC substrate.
[0056] The content of chain-like particles in the coating is preferably 3 to 15% by weight. If the content of chain-like particles is less than 3% by weight, there may be too few chain-like particles in the coating, resulting in a high surface resistance value. If the content of chain-like particles exceeds 15% by weight, the discoloration of the coating is more noticeable. The content of chain-like particles is more preferably 4 to 10% by weight.
[0057] The surface resistance of the film-coated substrate is 107 ~10 12 It is preferable that the surface resistance value be within the range of Ω / □. 7 To achieve a resistance of less than Ω / □, it is necessary to include many chain-like particles in the coating, which would result in insufficient coloring and hardness. 12 If the resistance exceeds Ω / □, the antistatic performance becomes insufficient. The surface resistance of the film-coated substrate is 10 8 ~10 12 It is more preferable that the ratio is Ω / □.
[0058] The film thickness is preferably 0.5 to 30 μm. If the film thickness is less than 0.5 μm, it is difficult to obtain sufficient surface resistance and hardness. If the film thickness exceeds 30 μm, cracks, curling (bending or warping), or discoloration may occur in the film. A film thickness of 1 to 15 μm is more preferable.
[0059] Film-coated substrates are manufactured by applying a coating to the substrate, drying it, and curing it. Well-known coating methods include the dip method, spray method, spinner method, roll coating method, bar coating method, slit coater printing method, gravure printing method, and microgravure printing method. Drying is performed at temperatures ranging from room temperature to approximately 90°C. When using UV-curable resins, the drying temperature is 100-1000 mJ / cm². 2 The resin is cured by ultraviolet irradiation.
[0060] When using an inorganic matrix consisting of a thermosetting resin or organosilicon compound, a curing treatment by heating may be performed. For example, the coating applied to the substrate may be heated to 150°C or higher during or after drying. When using an electron beam curable resin, the dried coating is irradiated with electromagnetic waves such as electron beams, X-rays, or gamma rays, which have a shorter wavelength than visible light. This accelerates the curing of the matrix-forming components, resulting in a higher hardness of the resulting coating.
[0061] The resulting film has low surface resistance, excellent adhesion to the substrate, transparency, and haze, and is less prone to cracking. [Examples]
[0062] The following describes an embodiment of this design.
[0063] [Example 1] <Preparation of ATO powder> A mixed solution was prepared by dissolving 10.4 kg of potassium stannate trihydrate and 2.2 kg of potassium antimonyl tartrate in 32 kg of pure water. This mixed solution was added to 75 kg of pure water containing 91 g of ammonium nitrate and 88 g of 85% potassium hydroxide at 30°C over 24 hours with stirring to carry out hydrolysis. During this time, a 10% aqueous nitric acid solution was added simultaneously to maintain the pH of the solution at 9.0. After filtering and washing the resulting precipitate, a dispersion of the precursor hydroxide (solid content concentration 20% by weight) was prepared by dispersing it again in water.
[0064] After drying this dispersion at 110°C, the resulting powder was heated at 550°C for 2 hours in an air atmosphere. This yielded ATO powder. The specific surface area of this ATO powder was 93 m². 2 The weight ratio of tin oxide to antimony oxide was 84:16.
[0065] <Preparation of a dispersion of chain-like particles> [Step a] 1875 g of this ATO powder was suspended in 4740 g of a 0.42 wt% potassium hydroxide aqueous solution. Subsequently, the suspension was dispersed for 9 hours using a bead mill filled with glass beads. The suspension was maintained at 30°C during the dispersion process. The ATO concentration of the resulting dispersion was 28.3 wt%. The amount of silicon dioxide in the dispersion was 1.0% of the ATO amount. The amount of alkali metals in the dispersion was 1.1% of the ATO amount.
[0066] 6000g of this dispersion was mixed with 18000g of pure water, and the dispersion was kept at 95°C for 5 hours and then cooled to room temperature. The dispersion was then centrifuged at 15200G for 10 minutes. The supernatant was then collected. This process removes coarse particles.
[0067] [Step b] A dispersion with a solid content of 6% by weight was prepared by adding pure water to the recovered supernatant. The dispersion was then subjected to hydrothermal treatment (175°C, 24 hours). The dissolved oxygen concentration before hydrothermal treatment was 8 mg / L. 3200 g of this dispersion was mixed with cation exchange resin until the pH reached 3.0, and the mixture was stirred for 60 minutes. The resin was then separated by filtration of the dispersion.
[0068] [Process c] Next, 15% aqueous ammonia was added to 3000g of this dispersion (solid content concentration 5.5% by weight) to adjust the pH to 8.0. After centrifuging the dispersion (15200G, 10 minutes), the supernatant was collected. This resulted in a dispersion from which coarse particles had been removed. Next, the solid content concentration of the dispersion was adjusted to 20% by weight using an ultrafiltration membrane. Furthermore, a cation exchange resin was added to the dispersion to adjust the pH to 3, and the dispersion was stirred for 30 minutes. After that, the resin was separated from the dispersion, and the dispersion was allowed to stand at 35°C for 12 hours.
[0069] [Step d] Next, 28 g of tetraethoxysilane (Tama Chemical Co., Ltd., orthosilicate ethyl, SiO2 concentration 28.8% by weight) was added to 800 g of this dispersion (solid content concentration 20.0% by weight) over 10 minutes, and the dispersion was stirred for 30 minutes. Furthermore, 800 g of ethanol was added to the dispersion, and the dispersion was stirred at 50°C for 15 hours. As a result, the solid content concentration became 10.3% by weight.
[0070] Next, the dispersion medium of the dispersion was replaced with ethanol using an ultrafiltration membrane, and then the dispersion was concentrated. This yielded an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) according to this example.
[0071] The preparation conditions for the ethanol dispersion of chain-like particles are shown in Table 3. Its physical properties were measured using the following method. The results for other examples and comparative examples are also shown in Table 4.
[0072] The isoelectric point of the chain-like particles in this example was 0.8, and the average particle size when the pH was adjusted to 1.0 was 18 nm.
[0073] (1) Isoelectric point The dispersion prepared in this example was diluted to 0.1% by weight with pure water. Hydrochloric acid (5% by weight) was added to this dispersion to adjust the pH to 0.1, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, and 4.0. This prepared samples with the above-mentioned pH values. The zeta potential of each sample was measured using a zeta potential measuring device (Zetasizer Nano ZS, Spectris). A graph showing the relationship between zeta potential and pH was created, and the pH at which the zeta potential was 0 was determined from the graph and defined as the isoelectric point.
[0074] (2) Average particle size at pH 1.0 A dispersion with a pH of 1.0 was prepared by adding hydrochloric acid (5% by weight) to the dispersion according to this example. The average particle size was determined by measuring this dispersion using a dynamic light scattering particle size distribution analyzer (NANOTRAC-WAVE II, Microtrac-Bell).
[0075] (3) Average particle size The dispersion from this example was diluted to 0.01% by weight by adding the same solvent as the dispersion. The resulting dispersion was dried on a collodion film of a copper cell for an electron microscope. This was then photographed at a magnification of 200,000x using a field emission transmission electron microscope (HF5000, Hitachi High-Technologies Corporation). The short axis of any 1000 chain-like particles was determined by image processing of the resulting photographic projection (TEM image), and the average value of the short axis was taken as the average particle diameter.
[0076] (4) Average number of connections Similar to the measurement of average particle diameter described above, 1000 chain-like particles were selected, and the major axis of each was determined. The average number of linked particles is the value obtained by dividing the "average major axis" by the "average minor axis (average particle diameter)" described above. Table 4 shows the integers obtained by rounding.
[0077] (5) Weight ratio of silicon dioxide, tin dioxide, and antimony dioxide The dispersion prepared in this example was dried at 120°C for 12 hours. Using an X-ray fluorescence analyzer (EA600VX, Hitachi High-Tech Science Corporation), the content of silicon dioxide (SiO2), tin oxide (SnO2), and antimony oxide (Sb2O5) in the dried material was determined, and their weight ratios were calculated.
[0078] <Paint production> A paint was prepared by thoroughly mixing 100 g of an ethanol dispersion of chain-like particles according to this example, 220 g of ethylene oxide-modified acrylic resin (NK ester ATM-4E, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), 94 g of 1,6-hexanediol diacrylate (unmodified acrylic resin, Kayarad KS-HDDA, manufactured by Nippon Kayaku Co., Ltd.), 16 g of photoinitiator (Omnirad-184, manufactured by IGM Resins BV), 490 g of isopropanol, 140 g of isopropyl glycol, and 140 g of butyl cellosolve. The preparation conditions for the paint are shown in Table 5. Unless otherwise specified, paints were prepared and evaluated in the same manner in subsequent examples and comparative examples.
[0079] <Preparation of coated substrates> This coating was applied to a PET film (Toyobo Co., Ltd. A-4300: 188 μm thick, total light transmittance of substrate 90.0%, haze 0.6%) using the bar coater method (#10). After drying the coating at 70°C for 120 seconds, it was subjected to a high-pressure mercury lamp treatment at 600 mJ / cm². 2 The film was cured by irradiation with ultraviolet light. The thickness of the resulting film-coated substrate was 5 μm.
[0080] The physical properties of the film-coated substrates were measured and evaluated as follows. The results are shown in Table 5. Unless otherwise specified, film-coated substrates were prepared and evaluated in the same manner in subsequent examples and comparative examples.
[0081] (6) Surface resistance The surface resistance of the film-coated substrate was measured using a surface resistance meter (Hyresta UX MCP-HT800, manufactured by Nitto Seiko Analytech Co., Ltd.).
[0082] (7) Transparency The total light transmittance and haze of the film-coated substrate were measured using a haze meter (NDH4000, manufactured by Nippon Denshoku Industries Co., Ltd.).
[0083] (8) Coloring The film-coated substrate was illuminated with fluorescent light and visually inspected. The presence or absence of coloration upon transmission was evaluated according to the following criteria. It is colorless and transparent, with no discoloration whatsoever: A Very slight discoloration is observed: B Slight discoloration is observed: C Dark discoloration is observed :D
[0084] (9) Adhesion 100 grids were created on the surface of a film-coated substrate by making 11 parallel scratches with a knife at 1 mm intervals vertically and horizontally. Cellophane tape was adhered to these grids, and then the cellophane tape was peeled off. The number of grids that remained with the film (residual grids) was then measured. Based on the number of residual grids, the adhesion was evaluated according to the following criteria. Number of remaining squares: 100 :A Number of remaining squares: 90-99 :B Number of remaining squares: 85-89 :C Number of remaining squares: 84 or less :D
[0085] (10) Scratch resistance Using steel wool (#0000), with a load of 1000g / cm² 2 The film surface was then rubbed 50 times. Scratch resistance was evaluated by visual observation according to the following criteria. No linear scars were observed: A Slight linear scarring is observed: B Numerous linear scars are observed: C The entire surface is worn down :D
[0086] [Example 2] ATO powder was prepared in the same manner as in Example 1. 1875 g of this ATO powder was suspended in 4740 g of a 0.42 wt% potassium hydroxide aqueous solution. 18.3 g of silica sol (JGC Cataloid SI-550, SiO2 concentration 20.5 wt%) was added to this suspension as silicon dioxide. Subsequently, the suspension was dispersed for 8 hours using a bead mill packed with zirconia beads. The suspension was maintained at 30°C during the dispersion process. The ATO concentration of the obtained dispersion was 28.3 wt%. The amount of silicon dioxide in the dispersion was 0.2% of the ATO amount. The amount of alkali metal in the dispersion was 1.1% of the ATO amount. Next, the dispersion was centrifuged in the same manner as in Example 1, and the supernatant was collected.
[0087] From this point onward, an ethanol dispersion of chain-like particles with a solid content of 30% by weight was prepared in the same manner as in Example 1. The isoelectric point of these chain-like particles was 1.6, and the average particle size when the pH was adjusted to 1.0 was 45 nm.
[0088] [Example 3] An ethanol dispersion of chain-like particles with a solid content of 30% by weight was prepared in the same manner as in Example 2, except that the amount of silica sol added as silicon dioxide in step a was changed to 457.3 g. The isoelectric point of these chain-like particles was 0.5, and the average particle size when the pH was adjusted to 1.0 was 15 nm. The ATO concentration of the dispersion after dispersion treatment was 26.5% by weight. The amount of silicon dioxide contained in the dispersion was 5.0% of the ATO amount. The amount of alkali metal contained in the dispersion was 1.2% of the ATO amount.
[0089] [Example 4] An ethanol dispersion of chain-like particles with a solid content of 30% by weight was prepared in the same manner as in Example 1, except that a 7.0% by weight potassium hydroxide aqueous solution was used in step a of Example 1. The isoelectric point of these chain-like particles was 0.4, and the average particle size when the pH was adjusted to 1.0 was 15 nm. The ATO concentration of the dispersion after dispersion treatment was 28.3% by weight. The amount of silicon dioxide contained in the dispersion was 4.9% of the ATO amount. The amount of alkali metal contained in the dispersion was 17.7% of the ATO amount.
[0090] [Example 5] The dispersion treatment was carried out in the same manner as in Example 2, except that the amount of silica sol added as silicon dioxide in step a was changed to 100.6 g. The ATO concentration of the dispersion after the dispersion treatment was 27.9% by weight. The amount of silicon dioxide contained in the dispersion was 1.1% of the ATO amount. The amount of alkali metal contained in the dispersion was 1.1% of the ATO amount. Next, the dispersion was subjected to centrifugation in the same manner as in Example 1, and the supernatant was collected.
[0091] Next, the supernatant was adjusted to a solid content of 10% by weight using an ultrafiltration membrane. This dispersion was then subjected to hydrothermal treatment (175°C, 24 hours). The dissolved oxygen concentration before hydrothermal treatment was 3 mg / L. From this point onward, an ethanol dispersion of chain particles with a solid content of 30% by weight was prepared in the same manner as in Example 1. The isoelectric point of these chain particles was 0.5, and the average particle size when the pH was adjusted to 1.0 was 95 nm.
[0092] [Example 6] In step a of Example 2, 24.4 g of Rheorosyl QS-20 (manufactured by Tokuyama Corporation, SiO2 concentration 99.9% by weight or higher) was added as silicon dioxide. Otherwise, a dispersion of ATO particles was prepared in the same manner as in Example 2. The ATO concentration of the dispersion after dispersion treatment was 28.2% by weight. The amount of silicon dioxide contained in the dispersion was 1.3% of the ATO amount. The amount of alkali metal contained in the dispersion was 1.1% of the ATO amount. Next, the dispersion was subjected to centrifugation treatment in the same manner as in Example 1, and the supernatant was collected.
[0093] Next, the supernatant was adjusted to a solid content of 15% by weight using an ultrafiltration membrane. Furthermore, bubbling with O2 gas was performed. Subsequently, the dispersion was subjected to hydrothermal treatment (175°C, 24 hours). The dissolved oxygen concentration before hydrothermal treatment was 20 mg / L or higher. To 3200 g of this hydrothermal-treated dispersion, a cation exchange resin was added until the pH reached 3.0, and the mixture was stirred for 60 minutes. The resin was then separated by filtration of the dispersion.
[0094] From this point onward, an ethanol dispersion of chain-like particles with a solid content of 30% by weight was prepared in the same manner as in Example 1. The isoelectric point of these chain-like particles was 0.2, and the average particle size when the pH was adjusted to 1.0 was 13 nm.
[0095] [Example 7] The process up to the hydrothermal treatment in step b was carried out in the same manner as in Example 1 to obtain a dispersion after hydrothermal treatment. 15% aqueous ammonia was added to 3000 g of this dispersion to adjust the pH to 4.0. After centrifuging (15200 G, 10 minutes) of this dispersion, the supernatant was collected to obtain a dispersion. Next, the solid content concentration of the dispersion was adjusted to 15% by weight using an ultrafiltration membrane. Furthermore, a cation exchange resin was added to the dispersion to adjust the pH to 3, and the dispersion was stirred for 30 minutes. After that, the resin was separated from the dispersion, and the dispersion was allowed to stand at 35°C for 12 hours.
[0096] Next, 20.8 g of tetraethoxysilane was added to 800 g of this dispersion (solid content concentration 15% by weight) over 10 minutes, and the dispersion was stirred for 30 minutes. Furthermore, 800 g of ethanol was added to the dispersion, and the dispersion was stirred at 50°C for 15 hours. As a result, the solid content concentration became 7.8% by weight.
[0097] Next, the dispersion medium of the dispersion was replaced with ethanol using an ultrafiltration membrane, and then the dispersion was concentrated. This yielded an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) according to this example. The isoelectric point of these chain-like particles was 0.8, and the average particle size when the pH was adjusted to 1.0 was 15 nm.
[0098] [Example 8] The process up to the hydrothermal treatment in step b was carried out in the same manner as in Example 1 to obtain a dispersion after hydrothermal treatment. 3000 g of this dispersion was mixed with 15% aqueous ammonia to adjust the pH to 10.0. This dispersion was subjected to centrifugation (15200 G, 10 minutes), and the supernatant was collected to obtain a dispersion. Next, the solid content concentration of the dispersion was adjusted to 30% by weight using an ultrafiltration membrane. Furthermore, a cation exchange resin was added to the dispersion to adjust the pH to 3, and the dispersion was stirred for 30 minutes. After that, the resin was separated from the dispersion, and the dispersion was allowed to stand at 35°C for 12 hours.
[0099] 800 g of this dispersion (solid content concentration 30% by weight) was mixed with 41.7 g of tetraethoxysilane over 10 minutes, and the dispersion was stirred for 30 minutes. Then, 800 g of ethanol was added to the dispersion, and the dispersion was stirred at 50°C for 15 hours. This resulted in a solid content concentration of 15.3% by weight.
[0100] Next, the dispersion medium was replaced with ethanol using an ultrafiltration membrane, and then the dispersion was concentrated. This yielded an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) according to this example. The isoelectric point of these chain-like particles was 0.8, and the average particle size when the pH was adjusted to 1.0 was 38 nm.
[0101] [Example 9] In step c of Example 1, the solid content concentration of the dispersion was adjusted to 20% by weight using an ultrafiltration membrane, thereby obtaining an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) according to this example. The isoelectric point of these chain-like particles was 0.8, and the average particle diameter when the pH was adjusted to 1.0 was 55 nm.
[0102] [Example 10] In step d, 18.8 g of tetraethoxysilane was added over 10 minutes to 300 g of the dispersion (solid content concentration 20.0 wt%) obtained in step c of Example 1, and the dispersion was stirred for 30 minutes. Furthermore, 300 g of ethanol was added to the dispersion, and the dispersion was stirred at 50°C for 15 hours. As a result, the solid content concentration became 10.6 wt%. The rest of the procedure was the same as in Example 1 to obtain an ethanol dispersion of chain-like particles (solid content concentration 30 wt%) according to this example. The isoelectric point of these chain-like particles was 0.6, and the average particle size when the pH was adjusted to 1.0 was 21 nm.
[0103] [Example 11] In step d, 12.4 g of 3-methacryloxypropyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) was added over 10 minutes to 300 g of the dispersion (solid content concentration 20.0% by weight) obtained in step c of Example 1, and the dispersion was stirred for 30 minutes. Furthermore, 1500 g of ethanol was added to the dispersion, and the dispersion was stirred at 50°C for 15 hours. As a result, the solid content concentration became 3.8% by weight. The rest of the procedure was the same as in Example 1 to obtain an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) according to this example. The isoelectric point of these chain-like particles was 0.7, and the average particle size when the pH was adjusted to 1.0 was 28 nm.
[0104] [Example 12] By performing the steps up to step b in the same manner as in Example 6, a dispersion with a solid content of 14.6% by weight was obtained. 500g of anion exchange resin was added to 3000g of this dispersion, and the dispersion was stirred for 1 hour. After separating the resin from this dispersion, 1000g of cation exchange resin was added again to the dispersion, and the dispersion was heated to 80°C and stirred. After cooling the dispersion to room temperature, the resin was separated from this dispersion.
[0105] 2800 g of this dispersion (solid content concentration 14.0 wt%) was mixed with 15% aqueous ammonia to adjust the pH to 8.0. After centrifuging this dispersion (15200 G, 10 minutes), the supernatant was collected. From this point onward, an ethanol dispersion of chain-like particles (solid content concentration 30 wt%) according to this example was prepared in the same manner as in Example 1. The isoelectric point of these chain-like particles was 0.2, and the average particle size when the pH was adjusted to 1.0 was 11 nm.
[0106] [Example 13] A mixed solution was prepared by dissolving 15.3 kg of potassium stannate trihydrate and 1.9 kg of potassium antimonyl tartrate in 43 kg of pure water. This mixed solution was added to 108 kg of pure water containing 131 g of ammonium nitrate and 93 g of 29% aqueous ammonia at 30°C over 24 hours with stirring to carry out hydrolysis. During this time, a 10% aqueous nitric acid solution was added simultaneously to maintain the pH of the solution at 8.5. After filtering and washing the resulting precipitate, it was dispersed again in water to obtain a dispersion of the precursor hydroxide (solid content concentration 20% by weight).
[0107] After drying this dispersion at 110°C, the resulting powder was heated at 550°C for 2 hours in an air atmosphere. This yielded ATO powder. The specific surface area of this ATO powder was 42 m². 2 The weight ratio of tin oxide to antimony oxide was 89:11.
[0108] From this point onward, an ethanol dispersion of the chain-like particles according to this example (solid content concentration 30% by weight) was prepared in the same manner as in Example 1, except that the amount of tetraethoxysilane added in step d was changed to 16.0 g. The isoelectric point of these chain-like particles was 1.2, and the average particle size when the pH was adjusted to 1.0 was 62 nm.
[0109] [Example 14] A mixed solution was prepared by dissolving 10.4 kg of potassium stannate trihydrate and 2.5 kg of potassium antimonyl tartrate in 32 kg of pure water. This mixed solution was added to 75 kg of pure water containing 91 g of ammonium nitrate and 88 g of 85% potassium hydroxide at 30°C over 24 hours with stirring to carry out hydrolysis. During this time, a 10% aqueous nitric acid solution was added simultaneously to maintain the pH of the solution at 11.0. After filtering and washing the resulting precipitate, a dispersion of the precursor hydroxide (solid content concentration 20% by weight) was prepared by dispersing it again in water.
[0110] After drying this dispersion at 110°C, the resulting powder was heated at 550°C for 2 hours in an air atmosphere. This yielded ATO powder. The specific surface area of this ATO powder was 145 m². 2 The weight ratio of tin oxide to antimony oxide was 82:18.
[0111] From this point onward, an ethanol dispersion of the chain-like particles according to this example (solid content concentration 30% by weight) was prepared in the same manner as in Example 1, except that the amount of tetraethoxysilane added in step d was changed to 40.0 g. The isoelectric point of these chain-like particles was 1.2, and the average particle size when the pH was adjusted to 1.0 was 62 nm.
[0112] [Example 15] A paint was prepared by thoroughly mixing 50 g of an ethanol dispersion of chain-like particles prepared in the same manner as in Example 1, 500 g of ethylene oxide-modified acrylic resin (NK ester ATM-4E, manufactured by Shin Nakamura Chemical Industry Co., Ltd.), 214 g of 1,6-hexanediol diacrylate (unmodified acrylic resin, Kayarad KS-HDDA, manufactured by Nippon Kayaku Co., Ltd.), 36 g of photoinitiator (Omnirad-184, manufactured by IGM Resins BV), 1470 g of isopropanol, 140 g of isopropyl glycol, and 140 g of butyl cellosolve.
[0113] [Example 16] A paint was prepared by thoroughly mixing 100 g of an ethanol dispersion of chain-like particles prepared in the same manner as in Example 1, 113 g of ethylene oxide-modified acrylic resin (NK ester ATM-4E, manufactured by Shin Nakamura Chemical Industry Co., Ltd.), 49 g of 1,6-hexanediol diacrylate (unmodified acrylic resin, Kayarad KS-HDDA, manufactured by Nippon Kayaku Co., Ltd.), 8 g of photoinitiator (Omnirad-184, manufactured by IGM Resins BV), 117 g of isopropanol, 140 g of isopropyl glycol, and 140 g of butyl cellosolve.
[0114] [Comparative Example 1] In step a of Example 1, the suspension was dispersed for 8 hours using a bead mill filled with zirconia beads. The ATO concentration of the resulting dispersion was 28.3% by weight. The amount of silicon dioxide contained in this dispersion was 0% of the ATO amount. The amount of alkali metal contained in the dispersion was 1.1% of the ATO amount. Next, the supernatant was collected in the same manner as in Example 1.
[0115] In step b, the supernatant liquid was adjusted using an ultrafiltration membrane to a solid content concentration of 15% by weight. The dispersion was then subjected to hydrothermal treatment (175°C, 24 hours). The dissolved oxygen concentration before hydrothermal treatment was 2 mg / L or higher. 1200 g of this dispersion was mixed with 2000 g of pure water, and then cation exchange resin was added until the pH reached 3.0. The mixture was stirred for 60 minutes. The resin was then separated by filtration of the dispersion.
[0116] This yielded a dispersion (solid content concentration 5.2% by weight). Using this dispersion, the process from step c onward was carried out in the same manner as in Example 1 to prepare an ethanol dispersion of chain-like particles (solid content concentration 30% by weight). The isoelectric point of these chain-like particles was 2.7, and the average particle diameter when the pH was adjusted to 1.0 was 181 nm.
[0117] [Comparative Example 2] In step a of Example 1, a 6.5% by weight potassium hydroxide aqueous solution was used. Otherwise, the procedure up to step a was the same as in Example 1. The ATO concentration of the dispersion after the dispersion treatment was 28.3% by weight. The amount of silicon dioxide in this dispersion was 7.1% of the ATO amount, and the amount of alkali metals in the dispersion was 25.3% of the ATO amount. Furthermore, the silicon dioxide content of the supernatant recovered in step a was 5.5% of the ATO amount.
[0118] A dispersion with a solid content of 6% by weight was prepared by adding pure water to the supernatant. The dispersion was then subjected to hydrothermal treatment (175°C, 24 hours). The dissolved oxygen concentration before hydrothermal treatment was 12 mg / L. This dispersion (3200 g) was washed with pure water using an ultrafiltration membrane until the pH reached 8.0.
[0119] 3000g of the obtained dispersion (solid content concentration 5.5 wt%) was subjected to centrifugation (15200G, 10 minutes), and the supernatant was collected. Next, the solid content concentration of the supernatant was adjusted using an ultrafiltration membrane to obtain a dispersion with a solid content concentration of 20 wt%. Furthermore, hydrochloric acid was added to the dispersion to adjust the pH to 3, and the dispersion was stirred for 30 minutes. After that, the dispersion was allowed to stand at 35°C for 12 hours.
[0120] From this point onward, an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) was prepared in the same manner as in Example 1. The isoelectric point of these particles was 0.4, and the average particle size when the pH was adjusted to 1.0 was 14 nm.
[0121] [Comparative Example 3] In step c of Example 1, the solid content concentration of the supernatant liquid recovered after centrifugation was adjusted to 13% by weight. Otherwise, an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) was prepared in the same manner as in Example 1. The isoelectric point of these particles was 0.8, and the average particle size when the pH was adjusted to 1.0 was 18 nm.
[0122] [Comparative Example 4] In step c of Example 1, the solid content concentration of the supernatant liquid recovered after centrifugation was adjusted to 20% by weight. A cation exchange resin was added to the resulting dispersion to adjust the pH to 4. Except for this, an ethanol dispersion of chain-like particles (solid content concentration 30% by weight) was prepared in the same manner as in Example 1. The isoelectric point of these particles was 0.8, and the average particle diameter when the pH was adjusted to 1.0 was 20 nm.
[0123] [Comparative Example 5] 3000g of the dispersion (solid content concentration 5.5% by weight) obtained in step b of Example 1 was subjected to centrifugation (15200G, 10 minutes) while maintaining the pH of 3, and the supernatant was collected. Subsequently, the supernatant was concentrated using an ultrafiltration membrane. However, at a solid content concentration of 12% by weight, the particles agglomerated and settled. Therefore, the process could not proceed to the next step.
[0124] [Comparative Example 6] In step c of Example 1, the solid content of the supernatant liquid recovered after centrifugation was adjusted to 35% by weight. A cation exchange resin was added to the resulting dispersion to achieve a pH of 3. This dispersion was then stirred, the resin separated, and allowed to stand, as in Example 1. Upon standing, the dispersion gelled. Therefore, the process could not proceed to the next step.
[0125] [Comparative Example 7] In step d of Example 1, 64 g of tetraethoxysilane was added over 10 minutes to 800 g of the dispersion (solid content concentration 20.0 wt%) obtained in step c. This dispersion was stirred for 30 minutes. Furthermore, 800 g of ethanol was added to the dispersion, and the dispersion was stirred at 50°C for 15 hours. This resulted in a solid content concentration of 10.7 wt%. From this point onward, an ethanol dispersion of chain particles (solid content concentration 30 wt%) was prepared in the same manner as in Example 1. The isoelectric point of these chain particles was 0.4, and the average particle size when the pH was adjusted to 1.0 was 16 nm.
[0126] [Table 3]
[0127] Table 4
[0128] Table 5
Claims
1. A dispersion of chain-like particles in which ATO particles are linked, The average particle size of the ATO particles is 5 to 20 nm. Silicon oxide in an amount of 0.2 to 5.0% relative to the mass of the ATO particles is provided on the surface of the ATO particles. The average number of linked chain particles is 3 to 40. A dispersion of chain particles, wherein the isoelectric point of the chain particles is less than pH 2.
0.
2. The aforementioned chain-like particles have an organosilicon compound represented by the following formula (1) on their surface, The dispersion of chain particles according to claim 1, wherein the sum of the mass of the silicon dioxide and the mass of the silicon dioxide component of the organosilicon compound is 0.5% or more and 10% or less with respect to the mass of the chain particles. R n -SiX 4-n (1) (In the formula, n is an integer from 0 to 3. R is an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, which may be the same or different from each other. The substituent is at least one of an epoxy group, a (meth)acryloyloxy group, a mercapto group, an amino group, a phenyl group, or an isocyanate group. X is at least one of an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, a halogen atom, or a hydrogen atom.)
3. A dispersion of chain-like particles according to claim 2, wherein the mass of tin oxide is 70 to 95% and the mass of antimony oxide is 4.5 to 29.5% of the total mass of silicon oxide, the silicon oxide component of the organosilicon compound, the tin oxide, and the antimony oxide.
4. The dispersion contains water or an organic solvent as a solvent. A dispersion of chain-like particles according to any one of claims 1 to 3, wherein the average particle diameter of the chain-like particles is 100 nm or less when an acid is added to the dispersion to adjust the pH to 1.
0.
5. A coating paint comprising the chain-like particles described in claim 1, a matrix-forming component, and an organic solvent.
6. A method for manufacturing a film-coated substrate, comprising the step of forming a film on a substrate using the paint described in claim 5.